1994
DOI: 10.1007/bf00196149
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar and argyrophilic nucleolar organizer region counts in urothelial carcinomas with special emphasis on grade II tumors

Abstract: Prognostic assessment of bladder carcinomas of intermediate differentiation is difficult. This study therefore investigated the prognostic values of nucleolar status and silver staining of argyrophilic nucleolar organizer regions (AgNORs) in grade II bladder carcinomas. In biopsies from 34 grade II transitional cell carcinomas of the urinary bladder the number of nuclei with nucleoli, the location of nucleoli within the nucleus and the number of AgNORs were determined in 1000 or 200 nuclei per section respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
3
4
0
1
Order By: Relevance
“…In this study, we also found that pAgNOR is more predictive of aggressive behaviour in astrocytoma grade III and glioblastoma multiform than mAgNOR. These findings are consistent with other reports of Helpap et al. (1994), Khan et al.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this study, we also found that pAgNOR is more predictive of aggressive behaviour in astrocytoma grade III and glioblastoma multiform than mAgNOR. These findings are consistent with other reports of Helpap et al. (1994), Khan et al.…”
Section: Discussionsupporting
confidence: 94%
“…1992, 1995), bladder carcinoma (Pich et al. 1992, 1995; Helpap et al. 1994), and skin melanocytic lesions (Pich et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the quantitative assessment of nuclear size, nuclear shape, nuclear roundness, nucleolar number, nucleolar size, and nucleolar shape, AgNOR staining, quantification of nuclear DNA content, and assessment of nuclear chromatin texture, predictive information may conceivably be obtained [19] ( Table 2). Through the quantitative assessment of nuclear size, nuclear shape, nuclear roundness, nucleolar number, nucleolar size, and nucleolar shape, AgNOR staining, quantification of nuclear DNA content, and assessment of nuclear chromatin texture, predictive information may conceivably be obtained [19] ( Table 2).…”
Section: Immunohistochemical and Molecular Markers For Stratificationmentioning
confidence: 99%
“…Beim Grad 1 (Grad 1b nach Subgrading; [15]) des papillären urothelialen Karzinoms haben neben der Zahl der Zelllagen (Epithelbreite) v. a. Kerngrößen und Kernformenvariabilität zugenommen, und die Kern-Plasma-Relation hat sich zugunsten der Kerne verschoben (Abb. 2).…”
Section: Papilläre Urotheliale Karzinomeunclassified